1984
DOI: 10.1152/ajpregu.1984.246.5.r832
|View full text |Cite
|
Sign up to set email alerts
|

Units in the amygdala responding to activation of carotid baro- and chemoreceptors

Abstract: The distribution of units in the amygdala responding to selective activation of baro- and chemoreceptors was investigated in 12 cats under alpha-chloralose anesthesia. Changes in the firing frequency of spontaneously discharging units were monitored during baroreceptor activation (BA) (phenylephrine hydrochloride, 2 micrograms/kg iv) and chemoreceptor activation (CA) (sodium cyanide, 25 micrograms in 0.1 ml saline into the medial thyroid artery). CA altered the firing frequency of 23% (35/154) of the units; 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Walker et al . (1953) and Weiskrant (1956) have shown that the amygdaloid complex plays an essential role in the genesis of emotions: (i) amygdalectomy results in several behavioural effects, including tameness, hypoemotionality, psychic blindness and changes in feeding and sexual behaviour referred as the Klüver–Bucy syndrome; (ii) amygaloid neurons are more sensitive to sensory events with biological and/or emotional significance (aversive or rewarding stimuli, faces); (iii) stimulation of the amygdala produces general arousal with a number of autonomic and behavioural defensive or aggressive responses [see review in Ledoux (1992)]. The amygdala appears to be involved in processing of aversive emotion.…”
Section: Discussionmentioning
confidence: 99%
“…Walker et al . (1953) and Weiskrant (1956) have shown that the amygdaloid complex plays an essential role in the genesis of emotions: (i) amygdalectomy results in several behavioural effects, including tameness, hypoemotionality, psychic blindness and changes in feeding and sexual behaviour referred as the Klüver–Bucy syndrome; (ii) amygaloid neurons are more sensitive to sensory events with biological and/or emotional significance (aversive or rewarding stimuli, faces); (iii) stimulation of the amygdala produces general arousal with a number of autonomic and behavioural defensive or aggressive responses [see review in Ledoux (1992)]. The amygdala appears to be involved in processing of aversive emotion.…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral lesions of the amygdala inhibit the response of corticosterone to several stimuli [6, 7, 8]with recent studies implicating the medial [9]and central [9, 10, 11]amygdaloid nuclei specifically. The central nucleus has also been shown to contain neurons that respond to cardiovascular inputs [12, 13, 14]and to project to several brain areas [15, 16, 17, 18]that influence the release of ACTH [19, 20, 21, 22]. …”
Section: Introductionmentioning
confidence: 99%
“…A major system involving cardiovascular regulation is the neuronal network that encompasses the baroreflex including peripheral receptors in the cardiac chambers, aorta and carotid sinus, medullary relay nuclei, and the efferent signals to the heart and vasculature. In addition, specific cortical regions associated with baroreceptor‐mediated cardiovascular function include the insular cortex (Butcher & Cechetto, 1995; Zhang et al 1999), anterior cingulate cortex (ACC) (Terreberry & Neafsey, 1987; Verberne & Owens, 1998), amygdala (Cechetto & Calaresu, 1983, 1984, 1985; Gelsema et al 1989) and the cerebellum (Bradley et al 1987 b ; Nisimaru et al 1998). There have been a limited number of cortical stimulation experiments performed in humans.…”
mentioning
confidence: 99%